Music Therapy and Music Medicine during Antenatal Period: Mechanisms and Evidence of Effects on Maternal and Fetal Health - Parmar, Parin N (Indian Journal of Integrative Medicine, 2021)
Music-based interventions, which include music therapy, music medicine, and other music-based interventions, are increasingly becoming popular in general population and health care professionals globally. In India, music and sounds have been used for health benefits since ancient time, but evidence-based music therapy as an allied health science is still in developing stage. Uniqueness of use of music-based interventions during antenatal care is due to their effects on both the expecting mother and the developing fetus; recent experiments related to effects of antenatal exposure of sounds and music on fetal neurodevelopment have particularly revealed interesting findings. The present article aims to discuss types of music-based interventions during antenatal period, their maternal and fetal effects and their possible mechanisms. Detailed description of music/music-based interventions and use of music-based interventions during labor, during post-natal period and for neonates/infants are not discussed